Natural Fiber-Reinforced Soil: A Brief Review Paper - Rizana, Rama; Rabbani, Arvin; Brillian, Afif Daffa; Agrina, Dwi; Listyawan, Anto Budi; Al-Amoudi, Omar Saeed Baghabra (ASTONJADRO, 2025)
The majority of building and civil engineering projects start on undeveloped soils. Before taking any further action, a thorough site inspection is required to determine the current condition of the site. Finding a location with optimal soil conditions can be difficult. One of the most commonly used methods for treating undeveloped soil is to incorporate natural fiber to reinforce soil, also known as natural fiber-reinforced soil. The purpose of this review article is to look at how different natural fibers reinforced soil. A review of studies suggests that reinforcing soil with natural fibers is a low-cost and effective stabilizing technique with several benefits. This paper is intended for geotechnical engineers in improving undeveloped soils with natural fibers, as well as researchers conducting future research.